Seawater carbonate chemistry and Magnesium (Mg/Ca, δ26Mg), boron (B/Ca, δ11B), and calcium (Ca2+ ) geochemistry of Arctica islandica and Crassostrea virginica extrapallial fluid and shell - Caraveo, Blanca Alvarez; Guillermic, Maxence; Downey-Wall, Alan; Cameron, Louise P; Sutton, Jill N; Higgins, John A; Ries, Justin B; Lotterhos, Katie; Eagle, Robert A (PANGAEA, 2025)
In this study, we investigated the geochemistry of three reservoirs important for biomineralization – seawater, the extrapallial fluid (EPF), and the shell – in two bivalve species: Crassostrea virginica and Arctica islandica. Additionally, we examined the effects of three ocean acidification conditions (ambient: 500 ppm CO2, moderate: 900 ppm CO2, and high: 2800 ppm CO2) on the geochemistry of the same three reservoirs for C. virginica. We present data on calcification rates, EPF pH, measured elemental ratios (Mg/Ca, B/Ca), and isotopic signatures (δ26Mg, δ11B). In both species, comparisons of seawater and EPF Mg/Ca and B/Ca, Ca2+, and δ26Mg indicate that the EPF has a distinct composition that differs from seawater. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-07-11.
Keywords: Animalia; Arctica islandica; Benthic animals; Benthos; Biomass/Abundance/Elemental composition; Calcification/Dissolution; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Crassostrea virginica; Laboratory experiment; Mollusca; North Atlantic; Single species; Temperate